Transfer as practice and creation force in artistic graphics: an experience from the mokulito technique (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This paper arises from my doctoral research on contemporary graphic arts, and it develops the idea that the different practices of contemporary printmaking are crossed by a constitutive and singular force specific to its field, which is the transference. In this sense, the analysis starts from the reflection on Deleuze's ideas about what the act of creation implies, specifically in the case of the act of creation of graphic arts. Transference acts as a creative force that articulates the practice and production of printmaking, beyond the regulations and functioning of each technique. In consequence, this paper presents the arguments why transference is considered an intrinsic and distinctive element of the practices of printmaking, which serves as an anchor for the analysis of what the development of this field of knowledge implies within the contemporary arts. Similarly, it includes an analysis of an experience of creating art prints using the mokulito technique from which the artist-researcher assumes his own practice of transference.
Keywords: Contemporary printmaking; transference; art practice; creative force; mokulito